Relationship of Placental TLR-7 Expression with Cord Blood HBV DNA and Placental HBV DNA - Naeny Fajriah; Maisuri T Chalid; Lenny Lisal; Efendi Lukas; St. Nur Asni; Rina Masadah (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2021)
Objective: To determine the role of TLR-7 expression on intrauterine vertical transmission in pregnancy through identification of serum hepatitis B markers in both maternal and umbilical cord blood.Method: Analysis of TLR expression was performed on 38 paraffin block samples of placental tissue acquired from mothers with HBV using TLR immunohistochemical staining.Result: 16 of 38 samples were acquired from mothers aged 26-30 years old. Most of the samples were from primiparous mothers (52.6%). This study found no significant association between TLR-7 expression and HBV DNA in the placenta and cord blood (p = 1.000). However, we found a significant association between placental TLR-7 expression and maternal HBV DNA (p = 0.034). Meanwhile, placental HBeAg and HBV DNA were not associated with placental TLR-7 expression (p = 0.082; p = 1.000).Conclusion: There was no significant association between TLR-7 expression and HBV DNA in the placenta and cord blood, but we found a significant association between TLR-7 expression and maternal HBV DNA. Hubungan Ekspresi TLR-7 Plasenta dengan HBV DNA Tali Pusat dan HBV DNA Plasenta AbstrakTujuan: untuk melihat peran ekspresi TLR-7 terhadap transmisi vertikal intrauterina pada kehamilan melalui identifikasi marker serum hepatitis B pada darah ibu dan talipusar.Metode: Analisis ekspresi TLR dilakukan pada 38 sampel blok paraffin jaringan plasenta ibu yang menderita HBV dengan memakai pewarnaan imuhohistokimia TLR.Hasil: 16 dari 38 sampel berusia 26-30 tahun. Sebagian besar sampel merupakan kelompok primipara (52.6%). Penelitian ini tidak menemukan hubungan yang signifikan antara ekspresi TLR-7 di plasenta dan HBV DNA darah tali pusat (p = 1.000). Tapi, kami menemukan hubungan yang signifikan antara ekspresi TLR-7 plasenta dan HBV DNA ibu (p = 0,034). Sedangkan HBeAg dan HBV DNA plasenta tidak berhubungan dengan ekspresi TLR-7 plasenta (p = 0,082; p = 1.000).Kesimpulan: Tidak ada hubungan yang signifikan antara ekspresi TLR-7 dan DNA HBV di plasenta dan tali pusat, tetapi kami menemukan hubungan yang signifikan antara ekspresi TLR-7 dan DNA HBV ibu. Kata kunci: toll-like receptor (TLR) 7, HBV DNA, tali pusat, plasenta, Hepatitis B, infeksi intrauterina